2016
DOI: 10.1016/j.cortex.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Charting moment-to-moment brain signal variability from early to late childhood

Abstract: Large-scale brain signals exhibit rich intermittent patterning, reflecting the fact that the cortex actively eschews fixed points in favor of itinerant wandering with frequent state transitions. Fluctuations in endogenous cortical activity occur at multiple time scales and index a dynamic repertoire of network states that are continuously explored, even in the absence of external sensory inputs. Here, we quantified such moment-to-moment brain signal variability at rest in a large, cross-sectional sample of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 82 publications
3
24
0
Order By: Relevance
“…Developmental EEG studies have shown a spectral power shift to higher frequencies, decreasing theta/alpha ratio and increasing alpha peak frequency by age (Benninger et al, 1984;Clarke et al, 2001;Gasser et al, 1988;Miskovic et al, 2015). There are also developmental changes of the brain networks indexed by strengthening long-range alpha connectivity (Miskovic et al, 2015;Knyazev et al, 2017) and increasing EEG variability with age, proceeding from the posterior to anterior areas of the brain (Miskovic et al, 2016). Our and stimulus-driven ventral attention network (VAN) are activated during inhibitory and attentional tasks (Stevens et al, 2007;see also reviews by Corbetta et al, 2008;Parks and Madden, 2013;Vogel et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental EEG studies have shown a spectral power shift to higher frequencies, decreasing theta/alpha ratio and increasing alpha peak frequency by age (Benninger et al, 1984;Clarke et al, 2001;Gasser et al, 1988;Miskovic et al, 2015). There are also developmental changes of the brain networks indexed by strengthening long-range alpha connectivity (Miskovic et al, 2015;Knyazev et al, 2017) and increasing EEG variability with age, proceeding from the posterior to anterior areas of the brain (Miskovic et al, 2016). Our and stimulus-driven ventral attention network (VAN) are activated during inhibitory and attentional tasks (Stevens et al, 2007;see also reviews by Corbetta et al, 2008;Parks and Madden, 2013;Vogel et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The technology to measure brain entropy has advanced over the last five years resulting in a growing literature using a variety of brain imaging techniques applied to understand normal and abnormal brain function [ 16 – 18 ]. Brain entropy can be measured from fMRI data, which consists of a series of successive MRI brain images taken over time.…”
Section: Introductionmentioning
confidence: 99%
“…Kaur et al, 2019;Miskovic et al, 2016;Mizuno et al, 2010). We hope that our 863practical example of coarse-scale biases thus highlights the dangers of resulting mismatches 864and motivate the adoption of scale-varying parameters.…”
mentioning
confidence: 76%